STUDI PUSTAKA PERKEMBANGAN DAN PENERAPAN MODEL MAKE A MATCH PADA PEMBELAJARAN DI SEKOLAH DASAR - Widya; Rahmad Salim; Riri Marfilinda (LP2M Universitas Adzkia, 2021)
The Make A Match Model which is an active learning model. This model emphasizes learning in groups that help one another, work together to solve problem. The purpose of this research is to examine the development and aplication of the Make A Match learning model, espacially in the last 10 years. The research method used in this research is literature study. The author collected more than 20 references related to the history, development, and implementation of the Make A Match model. Data collection techniques used through litersture study. The results of this study were obtained in journals published in the last 10 years. Make A Match model has a significant influence on the achievement of cognitive competencies and problem solving skills. Based on the results of reviews from these journals, the Make A Match model can be categorized as very suitable to be applied to learning in elementary schools based on the results of the study, the use of the Make A Match model in learning in elementary schools is stated to be very good.